Influencing identity-based political resistance: a comparative study on traditional poetics of Ireland and Telangana - Chiranjeevi, Mekala; Kumar Dhumal, Suraj Nand (European Public & Social Innovation Review, 2025)
Introduction: This study explores the role of folk songs as catalysts for identity-based political resistance movements through a comparative discourse analysis of traditional poetics from Ireland and Telangana, India. It begins from the premise that such cultural expressions are central to constructing collective identity and political mobilization. Methodology: Using critical discourse analysis, the study compares two key resistance songs: The West’s Asleep by Thomas Davis and a folk resistance song performed by Gaddar in Telangana. The analysis identifies rhetorical turns and symbolic modalities that operate similarly across distinct cultural contexts. Results: Both songs employ comparable narrative strategies, such as appeals to regional geography, historical memory, and calls for collective action, revealing a shared structure of discursive resistance. Discussion: Folk songs function as powerful tools of resistance by articulating emotional narratives that legitimize struggle, build a shared sense of identity, and historicize oppression. Despite differing geographic and cultural origins, these art forms reveal parallel mechanisms of political expression. Conclusions: The study underscores the importance of regionally rooted artistic forms as drivers of political resistance and offers valuable theoretical insights into the connections between culture, identity, and mobilization.